Apocalipsis de nuestro tiempo - Schoenberg, Arnold, 1874-1951 (Astarté, 2014)
"Apocalypse of our time" is an audiovisual creation that is structured from Julio Escámez's large-scale paintings and Arnold Schoenberg's musical composition, "The Transfigured Night". It is a documentary that builds a fiction and reveals the atrocities of the capitalist world, and how, through history and its changes, the inexorable transformation of social reality is manifested.--